Effective Self-Determination Practices for Students with Disabilities: Implications for Students with Visual Impairments. (March 2019) - Cmar, Jennifer L.
Introduction: Given the lack of self-determination research and curricula focusing on children and youths with visual impairments (i.e., those who are blind or have low vision), the purpose of this article was to review the literature on effective self-determination practices for students with other disabilities for applicability to students with visual impairments. Method: A narrative review was conducted that focused on six self-determination practices for students with disabilities. Studies of the effectiveness of these practices that were published in the year 2000 or later were included in the review. Results: A total of 14 articles were identified that focused on the following interventions: Self-Determined Learning Model of Instruction, Whose Future Is It Anyway?, Check and Connect, Self-Advocacy Strategy, Self-Directed Individualized Education Program, and Computer-Assisted Instruction. The levels of evidence supporting each intervention varied from potential to moderate, with none falling into the strong category. Discussion: Although several studies included at least one student with visual impairment, their results were not disaggregated by disability category. As a result, the existing literature does not allow for any specific conclusions to be made about the effects of these interventions on students with visual impairments. Additional research that evaluates self-determination interventions among this population is warranted. Implications for practitioners: By providing descriptions of six self-determination interventions and research evidence (including contextual information) supporting each one, this study serves as a starting point for practitioners to identify curricula that may be used to promote self-determination among their students. For students with visual impairments to fully benefit from these interventions, preteaching and accommodations by teachers of students with visual impairments or orientation and mobility specialists is necessary.